ChemInform Abstract: Iron‐Catalyzed Coupling of Aryl Sulfamates and Aryl/Vinyl Tosylates with Aryl Grignards. Issue 13 (March 2015) - Agrawal, Toolika; Cook, Silas P.
Abstract In contrast to previous reports with aryl chlorides, the title coupling reaction with aryl sulfamates proceeds with low levels of the Grignard homocoupling side reaction.